The Evolution of Cube Texture in Directionally Solidified Fe-3.0 wt. % Si Alloy Assisted by a High Static Magnetic Field - Chunmei Liu; Zijian Chen; Hongyu Li; Wenhao Lin; Meilong Feng; Tianxiang Zheng; Bangfei Zhou; Yunbo Zhong (Metals)
The effect of a high static magnetic field (HSMF) on the evolution of cube texture in directionally solidified Fe-3.0 wt. % Si alloy was studied. The results show that the <001> crystal orientation of an α-Fe single crystal was parallel to the direction of the HSMF, and a sharp cube texture was successfully formed in the final ingot. With the increase in growth speed, the main texture of the Fe-3.0 wt. % Si alloy evolved in the way of <001>→<081>→<120> along the pulling direction when an HSMF was applied. The orientation transition was attributed to the magnetocrystalline anisotropy of the α–Fe crystal during the directional solidification process. As a result of texture optimization, the specimens with an HSMF had higher saturation magnetization and permeability than the sample without an HSMF. Furthermore, a new creative method to tailor the cube texture of Fe-based alloys during the directional solidification process assisted by an HSMF is proposed.